Detection Algorithm of Airport Runway in Remote Sensing Images - Zhuzhong Yang; Jiliu Zhou; Fangnian Lang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This article describes a rapid detection method of the airport runway for remote sensing images. The specific algorithm implementation steps are: Firstly, we use the Otsu's method to separate the runway from the images. Then we use the fractional differential gradient operator, which has good anti-noise performance and effective edge extraction ability, to extract the edge information of image, and use automatic threshold to distinguish the edge of runway and other objects. Finally, we use the Hough algorithm to calculate the runway. This detection method of the airport runway, which greatly reduce the data operation and greatly enhance the computing speed, has advantage of good test results and fast speed. This paper shows that, as the study of fractional differential, the application of fractional calculus in a wider area will be successful. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.5000